Electric charge tomography imaging using finite-element method and pro-rata distribution - Thuku, I. T. (2013)
Tomography is a cross-sectional distribution of materials in some region of interest such as cross-section of a pipeline. The technology is widely applied in order to optimize the production efficiencies in process industries that uses pipeline for conveyance. In this paper the elements' and coordinates interpolation techniques of the finite-element method; Cartesian coordinate system, Gauss and Coulombs electrostatic laws were applied to model the system equation with sixteen electrodynamic sensors. However, Matlab program was designed to structurally mesh cross-section of the conveying pipeline into triangular elements which serves as the image pixels. From the modeled system equation, charge spatial sensitivity map for the problem domain was made. The sensitivity matrix obtained, was used to reconstruct the tomography image of the moving particles using Filtered Back Projection and Pro-rata distribution concepts. The combination of the filtered back projection and Pro-rata distribution concepts introduced in the paper, gave a good tomographic image that shows the concentration profile of moving particles through pipeline.